An analysis of groupthink and decision making in a collectivism culture: the case of a public organization in Tanzania. Issue 1 (4th May 2021) - Tarmo, Crecencia Godfrey; Issa, Faisal H.
Abstract : Purpose: Groupthink happens in-group decision-making processes whereby members of a group prematurely arrive at a decision that may indicate consensus but for the aim of protecting group harmony. This limits the contributions of the individuals' talents, ideas, competences and experiences to more effective decisions. Although there are a number of studies on predictors (forecasters) of groupthink, they do not consider the influence of the African cultural aspects of collectivism, high power distance and tolerance on groupthink that may characterise the decision-making context in African settings. It is in that context that this case study analyses groupthink in a public sector organization in Tanzania. Design/methodology/approach: This paper unveils the presence of groupthink predictors that can affect the quality of decisions made in groups within the Tanzania context. The study was conducted in one of the public institutions in Tanzania that is under the Ministry of Home affairs. The study population included Directors, Managers, Heads of units, District registration officers and other officials as shown in Table 1. These are the people who participate in decision-making processes in the organization and were drawn from different offices of the organization including the headquarter office, Kibaha Data centre, District Registration offices from different regions including Dares Salaam, Coast region, Arusha, Mtwara, Mwanza, Manyara, Mbeya, Singida, Dodoma, Geita, Lindi and Njombe – these 12 administrative regions are among the 27 regions that make up the Tanzania mainland. Through simple random and purposive sampling methods, a total of 97 participants participated effectively. The criterion for participation being participants must have been involved with at least one decision-making group experience. The choice of the organization was done on the basis that it is a relatively a new institution of importance; it was also possible to get from it the needed data. Findings: The results of the study show that there is the presence of groupthink predictors of high trust, conformity and promotional leadership in decision-making groups in the organization. Furthermore, the diversity of group members alone indicates to be insufficient reason to avoid Groupthink. It is suggested that other important factors might be at play in group decision making including the influence of African cultural characteristics. Research limitations/implications: This study was limited to only one institution. For a study of this nature to be undertaken access to data could be a very significant problem. Limiting it to one organization we are familiar with made it a bit easy to achieve access. Practical implications: Group decision making and groupthink are rarely in discourse in Africa. Tanzania is not isolated from the world, and being a country that unity is a cultural tenet that is promoted at every level from the family to national level (Rwegelera, 2003; Tripp, 1999) effects of groupthink is reasonably conspicuous because of the inbuilt national culture that has shaped people to be tolerant and accepting of different perspectives, ethnic groups, religious and races (Tripp, 1999). The same tolerance and acceptance may be transferred to decision-making groups and easily cause the occurrence of groupthink that can affect the quality of decisions made. Social implications: The Tanzania government has dedicated itself to putting strict measures to prohibit unethical and erroneous decisions that cost the nation including reducing employees' misconduct. The findings of this study indicate that there are hidden aspects like groupthink that are not reached by those measures yet ironically impacts the decisions made in organizations and in turn costs organizations and the country at large and calls for the government and its institutions together with the private sector to be awakened and alerted if they are dedicated and concerned about the quality of decisions they make. Originality/value: This is an original research work building on previous research. Some findings on groupthink and implications have Western origins. In Africa, we need to figure out what is making the continent not to make significant steps to change the social-economic environment. This study highlights to both African academics and leaders with no management background to make them understand groupthink as a phenomena that has implications to quality decisions. It will also prompt similar studies and therefore widen understanding on decisions making.